1980
DOI: 10.3181/00379727-164-40896
|View full text |Cite
|
Sign up to set email alerts
|

Renal Vasodilatation Caused by Captopril in Conscious Normotensive and Goldblatt Hypertensive Dogs

Abstract: Blood pressure and renal blood flow were monitored in conscious normotensive and two-kidney one-clip Goldblatt hypertensive dogs. Captopril administered IV in a single dose of 0.1 mg/kg to normotensives increased renal blood flow by 26.8 & 7.6% and decreased renal vascular resistance, but did not significantly change blood pressure. Cumulative doses of 0.1 and 0.2 mg/kg increased renal blood flow by 29.9 k 6.5%, and decreased renal vascular resistance and blood pressure significantly. Qualitatively similar cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 5 publications
2
17
1
Order By: Relevance
“…Hence, it is not surprising that ACEinhibitors such as trandolaprilat and perindoprilat significantly augment the endothelium-dependent relaxations evoked by the kinin (Vidal & Vanhoutte, 1988, and unpublished observations). These observations help to explain the conversion of the vasoconstrictor effect of bradykinin into a vasodilator response, as has been reported in vitro as well as the potentiation in vivo of the vasodilator effect of bradykinin (Adamski & Grega, 1988;Kikta & Fregly, 1982;Zimmerman et al, 1980 In the presence of 10-9 M bradykinin PG F20,L 2x 10-6M (c) Other endothelium-dependent vasodilators: Preliminary evidence suggests that certain ACEinhibitors can potentiate endothelium-dependent relaxations to some (e.g. acetylcholine, adenosine diphosphate), but not all (e.g.…”
Section: Endothelium-derived Relaxing Factormentioning
confidence: 86%
“…Hence, it is not surprising that ACEinhibitors such as trandolaprilat and perindoprilat significantly augment the endothelium-dependent relaxations evoked by the kinin (Vidal & Vanhoutte, 1988, and unpublished observations). These observations help to explain the conversion of the vasoconstrictor effect of bradykinin into a vasodilator response, as has been reported in vitro as well as the potentiation in vivo of the vasodilator effect of bradykinin (Adamski & Grega, 1988;Kikta & Fregly, 1982;Zimmerman et al, 1980 In the presence of 10-9 M bradykinin PG F20,L 2x 10-6M (c) Other endothelium-dependent vasodilators: Preliminary evidence suggests that certain ACEinhibitors can potentiate endothelium-dependent relaxations to some (e.g. acetylcholine, adenosine diphosphate), but not all (e.g.…”
Section: Endothelium-derived Relaxing Factormentioning
confidence: 86%
“…However, as reported by REGOLI et al (1962) andGROSS et al (1964), since the contralateral kidney is depleted of renin, it is possible that circulating, rather than intrarenal, angiotensin is responsible for this tonic influence, and since captopril also potentiates bradykinin, it is possible that kinins also have a greater influence on renal vascular tone in this type of hypertensive rats than in NCR. ZIMMERMAN et al (1980) have observed that captopril causes a greater hypotensive effect and an increase in plasma renin activity (PRA) in two-kidney, one-clipped hypertensive dogs, but that the vasodilative effect of captopril on the renal vascular area is not significantly different between hypertensive and control dogs. In explaining their results, they have described that other factors besides the degree of activation of renin-angiotensin system determine the renal vascular response to captopril.…”
Section: Discussionmentioning
confidence: 99%
“…Captopril also induces reduction of the total peripheral resistance with the lowering of arterial pressure in essential hypertension (FUJITANI et al, 1979;TARAZI et a!.,1980). However, hardly any study has been done on the dilative effects of captopril on various regional vascular areas except the study in two-kidney, oneclip renovascular hypertensive dogs by ZIMMERMAN et al (1980). They have reported that a similar dilative effect of captopril was observed in the renal vascular area of these hypertensive and normotensive control animals.…”
mentioning
confidence: 89%
“…ACE inhibitors are well known to reduce arterial pressure and have been used extensively for patients with hypertension. ACE inhibitors have been used to reduce blood pressure in animal models [12][13][14] and human hypertension. [15][16][17][18][19] In conclusion, these results suggest that hypotensive effects of SDG isolated from flaxseed is mediated through inhibition of angiotensin-converting enzyme.…”
Section: Discussionmentioning
confidence: 99%